Biomechanical and functional effects of shoulder kinesio taping® on cerebral palsy children interacting with virtual objects. Issue 6 (26th April 2019) - García-Hernández, N.; Corona-Cortés, J.; García-Fuentes, L.; González-Santibañez, R. Díaz; Parra-Vega, V.
Abstract: The reaching of objects is usually practiced by CP children in conventional or Virtual Reality-based therapies to enhance motor skill performance. Recently, Kinesio Taping® method has been studied to increase mechanical stability and improve functional movement of the upper limb; however, its influence on CP children´s upper limb motion has been rarely quantified due to lack of sensory measurement. Therefore, in this paper, we evaluate the biomechanical and functional effects of applying shoulder Kinesio Taping® on CP children in the reaching-transporting of virtual objects, by using a low-cost tracking device, exact robust differentiation of data and a simple nonlinear biomechanical dynamic model of the trunk and arm.